2000
DOI: 10.1073/pnas.97.16.8955
|View full text |Cite
|
Sign up to set email alerts
|

Ribozyme-mediated inhibition of HIV 1 suggests nucleolar trafficking of HIV-1 RNA

Abstract: T he expression of HIV type 1 (HIV-1) is controlled by a posttranscriptional mechanism. From a single primary transcript several mRNAs are generated. These RNAs can be divided into three main classes: unspliced 9-kb, singly spliced 4-kb, and the multiply spliced 2-kb RNAs. Each of these RNAs is exported to the cytoplasm for translation and, in the case of the 9-kb RNA, for packaging into virions (1). Normally, pre-mRNAs must undergo a splicing process to remove one or more introns before being exported to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 57 publications
3
98
0
2
Order By: Relevance
“…Although the actual localization of Rev itself to the nucleolus has yet to be shown to be essential for its role in HIV-1 replication, it appears that the nucleolus has a fundamental role to play in HIV-1 replication. Some elegant experiments using a hammerhead ribozyme targeted to the nucleolus and specific for HIV-1 RNA showed that HIV-1 RNA trafficking through the nucleolus is essential for HIV-1 replication (40). Similarly, nucleolar targeting of a RNA-based inhibitor of HIV-1 Tat (a second HIV-1 nucleolar protein) was also able to significantly decrease HIV-1 replication, confirming that nucleolar targeting of Tat is required for HIV-1 replication (41).…”
Section: Discussionmentioning
confidence: 88%
“…Although the actual localization of Rev itself to the nucleolus has yet to be shown to be essential for its role in HIV-1 replication, it appears that the nucleolus has a fundamental role to play in HIV-1 replication. Some elegant experiments using a hammerhead ribozyme targeted to the nucleolus and specific for HIV-1 RNA showed that HIV-1 RNA trafficking through the nucleolus is essential for HIV-1 replication (40). Similarly, nucleolar targeting of a RNA-based inhibitor of HIV-1 Tat (a second HIV-1 nucleolar protein) was also able to significantly decrease HIV-1 replication, confirming that nucleolar targeting of Tat is required for HIV-1 replication (41).…”
Section: Discussionmentioning
confidence: 88%
“…Rev is required for export of viral mRNA to the cytoplasm (1, 5), a process essential for virus replication (5,58). It has been suggested previously that HIV-1 RNA is trafficking through the nucleoli of cells, giving the nucleolus a critical role in HIV-1 RNA export (59). Therefore, it is important to study the mobility and affinity kinetics of Rev within the nucleolus.…”
Section: In Vivo Rev Multimerization By Fret 50173mentioning
confidence: 99%
“…Dicha colocalización condujo a una eficiencia de corte de cerca del 100% (Samarsky et al, 1999). Esta estrategia ha sido empleada igualmente con éxito en células humanas inhibiendo la replicación del HIV (Michienzi et al, 2000;. Otro factor clave que en este contexto determina la localización es el casete de expresión utilizado (revisado en Castanotto et al, 2000), y más concretamente el tipo de promotor, las modificaciones postranscripcionales in vivo de los dos extremos del transcrito, y las secuencias que lo flanquean.…”
Section: Otros Requisitos Que Idealmente Deberían Cumplir Las Ribozimunclassified
“…Las ribozimas de cabeza de martillo presentan una alta especificidad, pues se diseñan para que sus brazos hibriden con el RNA diana que debe contener un trinucleótido NHH (siendo N cualquier nucleótido y H cualquier nucleótido excepto G), haciendo improbable su acción sobre otros RNAs. Otra ventaja de las ribozimas es que en principio pueden dirigirse a los distintos compartimentos celulares en los que se encuentre el RNA diana (Sullenger y Cech, 1993;Samarski et al, 1999;Michienzi et al, 2000;. Además, las ribozimas tienen capacidad de recambio múltiple, pues una misma molécula de ribozima puede catalizar la degradación de varias moléculas de sustrato.…”
Section: Ribozimas De Cabeza De Martillo Versus Rnas Interferentesunclassified